Comparative study of three boil-off gas treatment schemes: From an economic perspective. (1st December 2019) - Bao, Junjiang; Yuan, Tong; Zhang, Lei; Zhang, Ning; Zhang, Xiaopeng
Highlights: Integration of boil-off gas treatment process with liquefied natural gas cold energy generation. Economic comparison of three boil-off gas treatment schemes are conducted. The effect of boil-off gas content, electricity price and interest rate on the net present value of systems. The applicable scope of different treatment processes is outlined. Abstract: Since the tanks and pipes of the liquified natural gas terminal cannot realize absolute insulation, the generation of the boil-off gas is inevitable. The existence of boil-off gas will threaten the production safety of the system, so it is necessary to properly treat it. However, the boil-off gas treatment system has the problems of high energy consumption and waste of liquified natural gas cold energy. There is no comprehensive comparison between different boil-off gas treatment schemes. To solve these problems, this paper firstly compares three different boil-off gas treatment schemes, including the two-stage boil-off gas recondensation system with pre-cooling (case 1), the integrated boil-off gas recondensation and liquified natural gas cold energy power generation system (case 2) and the combined boil-off gas fueled gas turbine and liquified natural gas cold energy power generation system (case 3). Then, the influence of electricity price, interest rate and boil-off gas content on the net present value of systems are explored. The results show that case 3 has the largest net power output, followed by case 2 and case 1. For example, when the boil-off gas content is 0.15, the net output power of case 3 is 34.05 MW, the net output power of case 2 is 0.15 MW, while the net output power of case 1 is −0.53 MW. Electricity price, interest rate and boil-off gas content have an important impact on the net present value of systems. The net present value of systems increases with increasing boil-off gas content, and decreases as interest rate increases. Under the same boil-off gas content and interest rate conditions, case 3 is more suitable when the electricity price is higher, while case 2 is more appropriate at the lower electricity price.